AGORA ABAIXE O SOM: UPPS, ordem e música na cidade do Rio de Janeiro - Soares da Silva, Luciane (Caderno CRH, 2014)
Desde a década de 70, nas favelas cariocas, boa parte da produção cultural e de entretenimento está diretamente ligada à música negra norte-americana, passando por releituras em sua estrutura rítmica e adaptando as letras para o cenário nacional. A favela tem ocupado um lugar decisivo na produção e consumo musical, principalmente nos bailes funk, ambientes propícios à suspensão dos problemas do cotidiano, interação entre diferentes classes sociais, geração de renda e lócus privilegiado para demonstração do poder das facções. A música, nesse contexto, torna-se importante forma de comunicação e passa a ocupar um lugar central nas discussões sobre ordem urbana. Os dados apresentados são resultado de entrevistas em favelas entre 2005 e 2009, e no retorno a campo em 2012. Serão analisadas letras classificadas como “proibidas”, documentos produzidos pelo Estado durante a implantação das UPPS e um número especial da revista do Instituto Brasileiro de Análises Sociais (Ibase) sobre o tema. PALAVRAS-CHAVE: Favela. Conflitos sociais. Cultura. Ordem urbana. Polícia. NOW LOWER THE SOUND: UPPS, order and music in the city of Rio de Janeiro Luciane Soares da Silva Since the 70s, the slums, much of the cultural production and entertainment, is directly linked to black American music, through readings in its rhythmic structure and adapting the lyrics to the national scene. The slum has played a decisive role in the musical production and consumption, especially in dances “funk”, environments conducive to the suspension of everyday problems, interaction between different social classes, income generation and privileged locus for demonstration of the power of the factions. The music in this context, it becomes important form of communication and now occupies a central place in discussions of order and right to the city. After the establishment of the Police Pacification Units (UPPS), changes relating to the dances have generated problems between patrons and police. Around music, important symbolic disputes occur, since the social control exercised by the state, with more intensity on the prom goers, between 14 and 30 years. At the same time, a significant amount of funk banned still circulate through the city, with reviews will Municipality of the city of Rio de Janeiro, the state government and the federal government by way of driving occupations. The data presented are the result of interviews in slums between 2005 and 2009, and return to the field in 2012. Will be analyzed letters classified as “prohibited”, documents produced by the state during initiation of UPPS, and a special issue of the Brazilian Institute for Social Analyses (IBASE) on the topico. KEYWORDS: Slum. Social conflicts. Culture. Urban order. Police. MAINTENANT BAISSE LE SON : UPPS, ordre et musique dans la ville de Rio de Janeiro Luciane Soares da Silva Depuis les années 70, dans les favelas de Rio de Janeiro, une bonne partie de la production culturelle et des divertissements est directement influencée par la musique noire nord-américaine marquée par une nouvelle lecture de sa structure rythmique et adaptant les paroles des chansons au scénario national. La favela occupe une place de choix dans la production et la consommation musicale, essentiellement dans les bals funk, ambiances propices à l’oubli des problèmes quotidiens, à l’interaction entre les différentes classes sociales, source de revenus et lieu privilégié pour la démonstration du pouvoir des factions. Dans ce contexte, la musique devient un moyen important de communication et occupe désormais une place centrale dans les discussions concernant l’ordre urbain. Les données présentées sont le résultat d’interviews faites dans les favelas de 2005 à 2009, puis d’un retour sur le terrain en 2012. On analyse les paroles considérées “interdites”, les documents produits par l’Etat pendant l’implantation des UPPS et un numéro spécial de la revue de l’Institut Brésilien d’Analyses Sociales (IBASE) édité sur ce thème. MOTS-CLÉS: Favela. Conflits sociaux. Culture. Ordre urbain. Police. <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff; display: inline ! important; float: none;"> <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br